Die Rias der galicisch-asturischen Küste Spaniens: Beobachtungen und Bemerkungen zu ihrer Entstehung. Prof. Dr. Wolfgang Panzer zum 65. Geburtstag gewidmet - Mensching, Horst (ERDKUNDE, 1961)
Adopting the local Spanish name of the Galician Asturian coastal regions where they occur frequently, the drowned lower parts of valleys have been termed rias. Their formation was often only seen in connexion with the geological development of the coast, and the advance of the sea into former river valleys was frequently explained as a consequence of tectonic subsidence of the coastal region. Most definitions of the term rias coast in geomorphological textbooks are based on this earlier interpretation. More recent publications take into account also the Quaternary eustatic sea level changes but in the interpretation of the present rias limit themselves to the consequences of the last, i. e. postglacial rise, the Flanders transgression, despite the fact that in a number of cases the existence of earlier Pleistocene beach terraces in the ria bays was noted and mentioned. On the basis of his own observations on the coasts of the Iberian peninsula in 1958 and 1959 and a critical use of existing publications, the author attempts in this paper to view the genesis of rias within the framework of coastal development during the Quaternary as a whole. In doing so the morphological consequences of the glacial-eustatic sea level changes must in particular be taken into consideration. The well developed beach terraces within the Spanish ria bays furnished important clues. A number of phases of the development can be disting uished. The fluviatile development in the high rainfall area of the granite-gneiss bloc of Galicia and the Paleozoic massif of Asturia was as a result of sea recessions during the glacial periods determined by erosion phases in the lower courses of the rivers. These are contrasted with the phases of drowning in the interglacial periods which resulted from transgressions of the sea. In the ria-genesis both phases together make up one development cycle. Owing to the retreat of the coastline - according to Pfannenstiel during the early Quaternary a consequence of epirogenic uplift of the land masses - which during the Pleistocene was interacted with by glacial-eustatic sea level changes, the morphology of the bays altered greatly. The ria bays of the early Quaternary, which were larger than those of today, derived from Pliocene bays and became with every cycle deeper, narrower and extending further towards the sea, facts which explain their present funnel shape. This development can be deduced from detailed analyses of the marine terraces within the rias. The present morphology of the rias can at any rate only be interpreted by considering it as the last stage in the sequence of development during the Quaternary. The postglacial rise of the sea level was in this sequence merely responsible for the present extent of drowning of the lower parts of the valleys. Besides these generally valid and major factors in the development of rias the role of geological-tectonic and climate-geomorphological processes within the coastal regions of Asturia and Galicia are also discussed. Some examples from these parts of the Iberian coast are demonstrated in extenso but further detailed investigations are necessary to account for the typological differences between the Rias Bajas and the Rias Altas as well as the narrow Asturian Rias.